2020
DOI: 10.3390/biom10071073
|View full text |Cite
|
Sign up to set email alerts
|

Isoprostanoid Profiling of Marine Microalgae

Abstract: Algae result from a complex evolutionary history that shapes their metabolic network. For example, these organisms can synthesize different polyunsaturated fatty acids, such as those found in land plants and oily fish. Due to the presence of numerous double-bonds, such molecules can be oxidized nonenzymatically, and this results in the biosynthesis of high-value bioactive metabolites named isoprostanoids. So far, there have been only a few studies reporting isoprostanoid productions in algae. To fill this gap,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 61 publications
1
28
0
Order By: Relevance
“…In the literature, variation in PhytoP levels has been reported in other plant matrices and in accordance to different varieties such as cocoa beans, nuts, and algae. León-Perez and his co-workers mentioned different profiles of PhytoP in relation to the clone of the cocoa bean (Theobroma cacao L). In this study, 31 clones of cocoa beans grown on different experimental farms were assessed.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…In the literature, variation in PhytoP levels has been reported in other plant matrices and in accordance to different varieties such as cocoa beans, nuts, and algae. León-Perez and his co-workers mentioned different profiles of PhytoP in relation to the clone of the cocoa bean (Theobroma cacao L). In this study, 31 clones of cocoa beans grown on different experimental farms were assessed.…”
Section: Resultsmentioning
confidence: 95%
“…Occurrence of PhytoPs was investigated in many foodstuffs and plant species such as almonds, algae, pistachio kernals, dark chocolates, coffee, and cocoa . However, their presence in DPF was not fully investigated.…”
Section: Introductionmentioning
confidence: 99%
“…It was recently shown that H 2 O 2 can trigger the production of isoprostanoids derived from C18, C20 and C22 in the marine diatom Phaeodactylum tricornutum, which may explain the EPA proportion reduction observed in Stauroneis sp. [59][60][61]. The response patterns were overall speciesspecific, which was also reflected in the relative positions of the treatments along the axes delineated by the PCA planes.…”
Section: Discussionmentioning
confidence: 95%
“…R. violacea showed however increases of both C18:0 and EPA, the former being an important precursor for the biosynthesis of LC-PUFAs in microalgae [58]. Isoprostanoids and oxylipins, which correspond to oxidised PUFAs, have attracted enhanced interests due to their cell signalling functions and potential beneficial effects [59]. It was recently shown that H 2 O 2 can trigger the production of isoprostanoids derived from C18, C20 and C22 in the marine diatom Phaeodactylum tricornutum, which may explain the EPA proportion reduction observed in Stauroneis sp.…”
Section: Discussionmentioning
confidence: 99%
“…Vigor et al [ 5 ] profiled isoprostanoids using liquid chromatography-mass spectrometry/mass spectrometry (LC-MS/MS) in four marine microalgae (the diatoms Chaetoceros gracilis and Phaeodactylum tricornutum , the cryptophyte Rhodomonas salina and the haptophyte Tisochrysis lutea ). Isoprostanoids are high-value bioactive metabolites resulting from the nonenzymatic oxidation of PUFAs (termed NEO-PUFAs).…”
mentioning
confidence: 99%